PENGARUH KUALITAS PELAYANAN DAN KEPUASANTERHADAP LOYALITAS: Studi pada Pelanggan Ayam Kampung Asep Farm di Pituruh - Asep Sanjaya (STIE Rajawali Purworejo, 2022)
This research aims to determine the influence of service quality on loyalty to Asep Farm customers in Pituruh partially, the influence of satisfaction on loyalty to Asep Farm customers in Pituruh partially, and the influence of service quality and satisfaction on loyalty to Asep Farm customers in Pituruh simultaneously. The data source uses a questionnaire. The population in this study were Asep Farm customers in Pituruh. The sampling technique used is saturated sampling. The sample used was 32 people. The data analysis technique used is multiple linear regression analysis, coefficient of determination, T test and F test. The results of the t test show: a) the t value of the service quality variable is greater than t table (7.206 > 1.699) or a sig value of 0.005 (< 0.05) This means that partially there is a positive and significant influence between service quality and loyalty so that the first hypothesis is accepted; b) the t value of the satisfaction variable is greater than t table (7.606 > 1.699) or the sig value is 0.005 (< 0.05), meaning that partially there is a positive and significant influence between satisfaction and loyalty so that the second hypothesis is accepted. The results of the F test show that the F value is 253.522, which is greater than 4, and the sig value is 0.000 (< 0.05), meaning that simultaneously there is a positive and significant influence between service quality and satisfaction on loyalty so that the third hypothesis is accepted.